The Successfulness of A Multidisciplinary Approach For Obstructive Sleep Apnea - Susianti, Noor Alia; Nathania, Caroline Evanthe; Prodjohardjono, Astuti; Vidyanti, Amelia Nur; Gofir, Abdul; Setyaningsih, Indarwati; Setyaningrum, Cempaka Thursina Srie; Sutarni, Sri (Academic Hospital Journal, 2025)
Background: Obstructive Sleep Apnea (OSA) is a global problem that has an impact on health and quality of life (QOL). There are a lot of risk factors for OSA, i.e. anatomical abnormality and comorbidity. A multidisciplinary approach can improve the symptoms and the impact of OSA and QOL too.Materials and methods: This case report is structured according to The CARE (Case Report) guideline.Case: A male, 37 years old, came with the chief complaint of snoring for 6 years. The patient felt unfit and dissatisfied with his sleep (Sleep Condition Indicator: 2.5). This impacted the daily activities and caused excessive daytime sleepiness. He could fall asleep while doing activities (Epsworth Sleepiness Scale: 24). The condition was worsening and he was often found apnea during sleep. The patient’s body mass index was 38.3kg/m2 (type I obesity) and the neck diameter was 43 cm. The polysomnography showed sleep architectural abnormality and the patients suffered from moderate OSA (Apnea-Hipopnea Index: 23.7). The patient was hospitalized for 7 days and got a Continuous Positive Airway Pressure Device (CPAP). Anatomical abnormality was investigated but none needed surgical intervention. Metabolic syndrome intervention includes therapy for hypertension, dyslipidemia, and diabetes. Collaboration with a clinical nutritionist for nutritional intervention. After 7 days, the sleep quality, the symptoms, and the SCI score were improved (7.1). Conclusion: OSA risk factors are varied and needed to be identified. In addition to definitive therapy, management of comorbidities, such as metabolic syndrome, should be addressed. A multidisciplinary approach can thereby improve OSA, patient’s health, and QOL.